Modeling ESG-Driven Sustainability Performance in the Steel Industry: Empirical Evidence from Thailand’s EEC - Thawornsujaritkul, Thitirat; Boonnual, Chutimant (Journal of Posthumanism, 2025)
Sustainability has become a critical priority for organizations worldwide, particularly in high-impact industries such as steel manufacturing. This study develops and validates a comprehensive measurement model for Environmental, Social, and Governance (ESG)-based sustainability performance in the steel sector. Using survey data from executives of steel manufacturing plants in Thailand’s Eastern Economic Corridor (EEC), the study applies Confirmatory Factor Analysis (CFA) and second-order modeling to examine the hierarchical structure of ESG dimensions. The model comprises of 45 indicators across 15 first-order constructs, grouped under three second-order ESG categories. Results confirm the robustness of the model, demonstrating strong validity and reliability across ESG constructs. The findings offer critical insights for policy-makers, corporate leaders, and sustainability practitioners in designing strategic interventions that align with global sustainability goals and industry-specific challenges.